PENAMPILAN TINGKAH LAKU SEKSUAL SAPI PEJANTAN LIMOUSIN DAN SIMMENTAL DI BALAI INSEMINASI BUATAN LEMBANG - Sam, Achmad F; Pudjihastuti, E .; Hendrik, M J; Ngangi, L R; Raka, I G.P.N (Universitas Sam Ratulangi, 2017)
ABSTRACT SEXUAL BEHAVIOR OF LIMOUSIN AND SIMMENTAL BULL BREEDSAT THE LEMBANG ARTIFICIAL INSEMINATION CENTER. In order to provide the prominent bulls, the management process of animal selection was required for animal replacement stock. Animal selection was including the inspection of animal physical and sexual behavior. Based on this criterion, study was conducted to observe the sexual behavior of Limousin and Simmental breed bulls at the artificial insemination center in Lembang, Bandung. The objective of this study was to evaluate the characteristic of sexual behavior of the Limousin and Simmental breed bulls. The amount of 80 bulls consisted of 40 Limousin and 40 Simmental bulls at the age of 6 to 9 years old were used in this study. Data collections were conducted by focal animal sampling. Sexual behavior was observed during ten days at the time from 07.00 to 11.00 West Indonesian Time. Data collection were started at the period of bull was introduced into teaser.Based on t-test on sexual behavior of Limousin and Simmental bulls, the results showed that (1) The time need for courtship with teaser of Limousin bull was significantly shorter (P<0,01) compared with Simmental bull; (2) Time period use for the first time to start flehmen of Limousin bull was shorter significantly (P<0,01) compared with Simmental bull; (3) Flehmen frequency of Limousin and Simmental was non significantly.Based on the observation of sexual behavior, the Limousin bull need time of the 2,22 seconds to start courthip with teaser, while Simmental bull need time of 2,77 seconds to start courtship with teaser. The Limousin bull need time of 222 seconds to start flehmen, while Simmental bull need time of 239 seconds to start flehmen. The time periods used for the first time to mount teaser by Limousin bull were 214,87 seconds, while those by Simmental bull were 302,02 seconds. The flehmen frequency of Limousin dan Simmental bulls was similar of only one time during sexual behavior.Key Words :Limousin, Simmental, Sexual behavior, Lembang Artificial Insemination Center